Optimizing Recovery in Oral Flap Surgeries: The Undervalued Role of Physiotherapy - Srivatsan Munusamy; Shenbaga Sundaram Subramanian; Tamil Ponni Sivamani; Surya Vishnuram (Rambam Maimonides Medical Journal, 2025)
To the Editor,